Higher resolution cine imaging with compressed sensing for accelerated clinical left ventricular evaluation. Issue 6 (26th October 2016) - Lin, Aaron C.W.; Strugnell, Wendy; Riley, Robyn; Schmitt, Benjamin; Zenge, Michael; Schmidt, Michaela; Morris, Norman R; Hamilton‐Craig, Christian
Abstract : Purpose: To assess the clinical feasibility of a compressed sensing cine magnetic resonance imaging (MRI) sequence of both high temporal and spatial resolution (CS_bSSFP) in comparison to a balanced steady‐state free precession cine (bSSFP) sequence for reliable quantification of left ventricular (LV) volumes and mass. Materials and Methods: Segmented MRI cine images were acquired on a 1.5T scanner in 50 patients in the LV short‐axis stack orientation using a retrospectively gated conventional bSSFP sequence (generalized autocalibrating partially parallel acquisition [GRAPPA] acceleration factor 2), followed by a prospectively triggered CS_bSSFP sequence with net acceleration factor of 8. Image quality was assessed by published criteria. Comparison of sequences was made in LV volumes and mass, image quality score, quantitative regional myocardial wall motion, and imaging time using Pearson's correlation, Bland–Altman and paired 2‐tailed Student's t ‐test. Results: Differences (bSSFP minus CS_bSSFP, mean ± SD) and Pearson's correlations were 14.8 ± 16.3 ( P  = 0.31) and r  = 0.98 ( P < 0.0001) for end‐diastolic volume (EDV), 8.4 ± 11.3 ( P  = 0.54) and r  = 0.99 ( P < 0.0001) for end‐systolic volume (ESV), –0.4 ± 2.5 ( P  = 0.87) and r  = 0.97 ( P < 0.0001) for EF, and –0.9 ± 11.8 ( P  = 0.92) and r  = 0.97 ( P < 0.0001) for LV mass. Bland–Altman analyses [bias and (limits of agreement)] revealed strong agreement in LVEDV [8.7 ml, (–12.1, 29.6)], LVESV [4.3 ml, (–11.9, 20.6)], LVEF [‐0.02%, (–5.37, 5.33)], and myocardial mass [‐6.1 g, (–14.7, 26.9)]. Image quality was comparable with a similar mean score ( P  = 0.42), with a good correlation in image quality observed ( r  = 0.68, P < 0.0001). Quantitative regional myocardial wall motion demonstrated strong correlation between the sequences ( r  = 0.87, P < 0.0001). Imaging time was significantly shorter for the CS_bSSFP sequence (1.1 ± 0.5 versus 5.6 ± 1.6 min, P < 0.0001). Conclusion: The novel high‐resolution cine CS_bSSFP accurately and reliably quantitates LV volumes and mass, shortens acquisition times, and is clinically feasible. Level of Evidence : 1 Technical Efficacy : Stage 2 J. MAGN. RESON. IMAGING 2017;45:1693–1699